Cryo multi-scale microscopy visualization tools for studying microbial communities on glacier surfaces - Mourot, Rey; Roddatis, Vladimir; Anesio, Alexandre M.; Tranter, Martyn; Benning, Liane G. (Frontiers in Earth Science, 2025)
In recent decades, a growing body of research has focused on characterizing supraglacial microbial communities. These studies have unveiled that pigmented glacier ice algae, namely, Ancylonema nordenskiöldii and Ancylonema alaskanum, blooming during the summer melt seasons accelerate surface melting. Most techniques that quantify microbial processes on glacial surfaces require the melting of samples prior to their analysis and, so far, the structure and three-dimensional arrangement of microorganisms that bloom on bare ice surfaces have never been characterized. To address this gap, we developed, tested and validated a first characterization workflow for imaging the microorganisms colonizing the frozen ice surfaces on the Greenland Ice Sheet. While preserving their frozen state, we employed a suite of microscopic tools with progressively increasing resolution, starting from imaging algae on ice with hand-held, portable microscopes (up to ×150 magnification) all the way to high-resolution cryo-scanning electron microscopy (cryo-SEM, up to ×5.000 magnification). Our images provided us with the first visualization of the distribution, structure, interactions, and relationship between microbes, minerals, and their frozen substrate. Our innovative approach significantly advances the understanding of glacial microbial life within the ice matrix, shedding light on the spatial architecture of microbial cells in their on-ice state, thereby improving how we perceive and study these unique ecosystems.